PULMONARY ARTERIOVENOUS MALFORMATION (PAVM): RARE CAUSE OF HEMOPTYSIS - Majeed, Farhan Ahmed; Ghumman, Adeel Qamar; Chatha, Sohail Saqib (Journal of Ayub Medical College Abbottabad, 2013)
Pulmonary arterio-venous malformation is an abnormal communication between pulmonary arteries and pulmonary veins. These lesions are rare and are an important part of the differential diagnosis of common pulmonary problems such as hypoxemia and pulmonary nodules. Pulmonary arterio-venous malformation was diagnosed in a 33 year old man who presented with recurrent episodes of haemoptysis and also had taken anti-tuberculous treatment (ATT) before. Pulmonary angiography revealed fistulous communication between right bronchial artery and right pulmonary vein. He was treated by lobectomy. Keywords: Arterio-venous malformations, Angiography, Lobectomy